2009 8th IEEE International Symposium on Mixed and Augmented Reality 2009
DOI: 10.1109/ismar.2009.5336501
|View full text |Cite
|
Sign up to set email alerts
|

Influence of visual and haptic delays on stiffness perception in augmented reality

Abstract: Visual delays are unavoidable in augmented reality setups and occur in different steps of the rendering pipeline. In the context of haptic interaction with virtual objects, it has been shown that delayed force feedback can alter the perception of object stiffness. We hypothesize that delays in augmented reality systems can have similar consequences. To test this, we carried out a user study to investigate the effect of visual and haptic delays on the perception of stiffness. The experiment has been performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 15 publications
1
21
0
1
Order By: Relevance
“…It was shown that delays in the visual modality alone caused an increase in perceived surface stiffness and that delays in the haptic modality alone caused a decrease in perceived surface stiffness. Simultaneous delays in both the visual and haptic modalities are shown to partly cancel out these changes in perceived surface stiffness [14].…”
Section: B Cognitive Limitationsmentioning
confidence: 90%
“…It was shown that delays in the visual modality alone caused an increase in perceived surface stiffness and that delays in the haptic modality alone caused a decrease in perceived surface stiffness. Simultaneous delays in both the visual and haptic modalities are shown to partly cancel out these changes in perceived surface stiffness [14].…”
Section: B Cognitive Limitationsmentioning
confidence: 90%
“…Although the visual feedback provided in AR differs greatly from VR, the same perceptual bias concerning depth or distance estimation has also been observed in AR [8]. Then, Knorlein et al [11] observed that a delay in force-feedback in AR could give the impression that a virtual object was softer. A similar effect had also been found in a VR context [16].…”
Section: Related Workmentioning
confidence: 95%
“…It has been shown, for example, in [21] and [22], that when haptic delays are present, the person using the haptic device perceives the force feedback to be weaker than it is in actuality. In order for the operator to feel the forces with the strength that they were intended to have, the delay caused by the computation of the force feedback should be minimized.…”
Section: Haptic Swarm Controlmentioning
confidence: 99%